Maloclusión, trastorno temporomandibular y su asociación a la cervicalgia - Vega Bazán, Liliana (2015)
Abstract Objective: This study has aimed to estimate the association between malocclusion and temporomandibular disorder with neck pain in patients seen in the area of odontology in an Odontology clinic. Materials and methods: A cross-sectional was performed in Lima, Peru. The population was composed of patients attending a dental clinic. During the last three months, assessment was made of self-reported neck pain, the temporomandibular disorder (TMD) with the index of Fonseca, types of malocclusion with dental assessment recorded in their medical history, oral habits and lack of teeth. The association was evaluated by estimating the established prevalence reasons (RPa). Results: The study included 215 people, whose mean age was 33.1±12.4 years old. Most of the subjects were women (69.3%). Prevalence of neck pain was 64.2%, 79.1% had some degree of TMD and 97.7% malocclusion. Having TMD was associated with neck pain, both moderate as severe (OR: 6.65, 95% CI: 3.17-3.95) and mild (OR: 4.88 95%, 95% CI: 2.29-10.41). No association between malocclusion and neck pain (95% CI: 0, 71-1, 13 OR 0.89) was found. Another associated factor was the absence of 3 or more teeth (OR: 1.25, 95% CI 1.01-1.56). Conclusions: Neck pain is associated with TMD but not with malocclusion. Therefore, a coordinated work between dentists and physiotherapists in the management of TMD and neck pain is recommended in order to comprehensively treat these patients.